A Practical and Robust Zwitterionic Cooperative Lewis Acid/Acetate/Benzimidazolium Catalyst for Direct 1, 4‐Additions. Issue 13 (14th February 2023) - Hans, Andreas C.; Becker, Patrick M.; Haußmann, Johanna; Suhr, Simon; Wanner, Daniel M.; Lederer, Vera; Willig, Felix; Frey, Wolfgang; Sarkar, Biprajit; Kästner, Johannes; Peters, René
Abstract: A catalyst type is disclosed allowing for exceptional efficiency in direct 1, 4‐additions. The catalyst is a zwitterionic entity, in which acetate binds to Cu II, which is formally negatively charged and serving as counterion for benzimidazolium. All 3 functionalities are involved in the catalytic activation. For maleimides productivity was increased by a factor >300 compared to literature (TONs up to 6700). High stereoselectivity and productivity was attained for a broad range of other Michael acceptors as well. The polyfunctional catalyst is accessible in only 4 steps from N ‐Ph‐benzimidazole with an overall yield of 96 % and robust during catalysis. This allowed to reuse the same catalyst multiple times with nearly constant efficiency. Mechanistic studies, in particular by DFT, give a detailed picture how the catalyst operates. The benzimidazolium unit stabilizes the coordinated enolate nucleophile and prevents that acetate/acetic acid dissociate from the catalyst. Abstract : Intramolecular cooperation of Cu II, coordinated acetate and a benzimidazolium unit in the catalyst periphery allows for unprecedented catalyst productivity and high stereocontrol in direct 1, 4‐additions to maleimides and a number of other Michael acceptors. Next to the sophisticated activation principle, the catalyst is readily prepared and has robust reactivity. Moreover, it is shown to be reusable multiple times.